2011
DOI: 10.1073/pnas.1017719108
|View full text |Cite
|
Sign up to set email alerts
|

Tonic inhibition of chronic pain by neuropeptide Y

Abstract: Dramatically up-regulated in the dorsal horn of the mammalian spinal cord following inflammation or nerve injury, neuropeptide Y (NPY) is poised to regulate the transmission of sensory signals. We found that doxycycline-induced conditional in vivo (Npy tet/tet ) knockdown of NPY produced rapid, reversible, and repeatable increases in the intensity and duration of tactile and thermal hypersensitivity. Remarkably, when allowed to resolve for several weeks, behavioral hypersensitivity could be dramatically reinst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 40 publications
8
131
1
Order By: Relevance
“…[25][26][27][28] In addition, and as discussed in the remainder of this review, there are PTSD-related neurohormones, neurotransmitters, and inflammatory system factors that impact pain transmission and/or amplification along the neuroaxis from the periphery to the brain and behavioral reactions that result. NPY and the GABAergic neuroactive steroids, [29][30][31][32][33][34][35][36][37][38] as well as the opioid and endocannabinoid systems, immune factors, and specific cellular second messenger systems (see below) thus appear to play roles in the pathophysiology of both PTSD and CP. As such, these systems may constitute pathophysiological domains that promote the comorbidity of these conditions.…”
Section: The Shared Neurobiology Of Chronic Pain and Ptsd: A Working mentioning
confidence: 96%
“…[25][26][27][28] In addition, and as discussed in the remainder of this review, there are PTSD-related neurohormones, neurotransmitters, and inflammatory system factors that impact pain transmission and/or amplification along the neuroaxis from the periphery to the brain and behavioral reactions that result. NPY and the GABAergic neuroactive steroids, [29][30][31][32][33][34][35][36][37][38] as well as the opioid and endocannabinoid systems, immune factors, and specific cellular second messenger systems (see below) thus appear to play roles in the pathophysiology of both PTSD and CP. As such, these systems may constitute pathophysiological domains that promote the comorbidity of these conditions.…”
Section: The Shared Neurobiology Of Chronic Pain and Ptsd: A Working mentioning
confidence: 96%
“…Conditional knockout mice lacking NPY in the spinal cord and sensory neurons in adulthood lack tonic, long-lasting inhibitory control of spinal nociceptive transmission by NPY. 140 NPY administration in rats attenuates morphine-induced tolerance and withdrawal symptoms in neuropathic pain model, suggesting an interaction with the endogenous opioid system. 141 The antinociceptive actions of NPY are described to be similar to the opioid family in pain alleviation.…”
Section: Painmentioning
confidence: 99%
“…What could be the functional significance of expression of NPY? Data from several studies, including experiments using doxycycline-induced knockdown of NPY, convincingly showed that NPY could act as an "endogenous braking mechanism" and suppress transmission of noxious stimuli at the spinal cord level [29][30][31]. The initial decrease of NPY immunostaining between 1 and 3 h after incision, when nociception was at its highest level, can be correlated with the release of NPY from synaptic terminals as well as extrasynaptic sites [32].…”
Section: Discussionmentioning
confidence: 99%